Determinants of, and the relationship between FDI and economic growth in Bangladesh - Mazbahul Golam Ahamed; Fahian Tanin (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
Inward FDI to the middle-income countries has the evidence as a major stimulus to the economic growth; conventionally at export-oriented manufacturing sector. In point of fact, basic macro fundamentals like as growth of gross domestic capital formation, foreign reserve, infrastructure etc. accelerates the FDI inflows. This study reviews the long-run trend on the time scale of FDI to Bangladesh over the period 1975- 2006 and major factors determining foreign companies' decisions to invest, in associated with economic growth. Contents of the paper describe the theoretical development and extensive literature review to find out the appropriate variables to deter the foreign direct investment from time series data. On the basis of intricate link between foreign direct investment and growth, all explained determinants enhance the facilitation, turnover, and return in FDI concentrated sectors that promote long-term sustainable growth with specific shortcomings, directly or indirectly, in our labor-intensive economic activity. Reduced government's ineffectiveness along with supporting policy framework makes Bangladesh as an attractivedestination of FDI, that has a positive spillover and significant impacts affect over time through dynamic effects on economic growth.
Keywords: 330; FDI; Determinants; Economic Growth; Bangladesh; Direktinvestition; Ausländisch; Wirtschaftswachstum; Schätzung; Bangladesch